(untitled) (Papeles, 2021)
We share some conclusions of my PhD thesis on «The Right to a Health Environment in Buenos Aires City. Citizen participation in its defense (1996–2019)» which demonstrates the importance of environmental law in cities, how Urban planning cannot be separated from Nature on which it is based, how extractivism has advanced on cities, breaking balance, its current serious consequences and the defense of Nature as a common good by urban citizens. It is an urgent environmental problem to be addressed since Argentina is one of the countries in the world and the region with the highest population concentration in cities (92 % is concentrated in 16 cities) and there are specific urban environmental problems each time more pressing (humble neighborhoods, consumerism, waste, lack of green spaces, air and water pollution, casing of streams, cementing wetlands, floods, excessive energy use of fossil fuels, depredation of natural, cultural and architectural heritage, among others). We incorporate the new ecocentric Latin American perspectives within the framework of a critical vision to traditional institutes of environmental law, traditional urban planning and the rule of law itself. We make proposals to improve participatory democracy, participatory law drafting and an Environmental Impact Assessment Minimum Standards Law.